Effect of Aerobic Exercise Circuit Training Programme on Primary Dysmenorrhea in Adolescent Girls - SHANMUGANANTH, E.; DILAXSHANA; K, REKHA. (International Journal of Psychosocial Rehabilitation, 2020)
Difficult menstrual flow or pain associated with menstruation is dysmenorrhea. It can be divided into two- primary Dysmenorrhea and secondary Dysmenorrhea. Of two, primary dysmenorrhea is the most common cause of abdominal pain and increased blood pressure. For almost half a century, physical exercise has been taught to help in relieving symptoms of pain induced dysmenorrhea, and in recent years researches regarding the inter-connection between aerobic exercise and dysmenorrhea have significantly increased due to its positive outcome. Hence, the purpose of this study is to determine the effectiveness of circuit training programme on pain and blood pressure on people with dysmenorrhea. 44 girls aged 18-26 years, who complained of pain during their menstruation, were recruited. Their pain level was assessed with numerical pain rating scale (NPRS) along with their systolic and diastolic blood pressures using sphygmomanometer. Secondary dysmenorrhea cases, people involved in gym and other physical activities and irregular menstrual cycle cases were excluded. People were trained with Aerobic circuit training programme. Circuit consisted of walking (10 min), jogging (10 min) and cycling (10 min) for 8 weeks, 4days/week. Pain (NPRS) and BP were measured pre-and post-intervention. There is a marked decrease in NPRS and blood pressure following circuit training programme which consisted of walking, jogging and running. There is a significant decrease in the symptoms associated with Dysmenorrhea on young girls who were following Circuit Training Programme.